Insufficient intake of alpha-linolenic fatty acid (18:3n-3) during pregnancy and associated factors - VASCONCELOS,Letícia Garcia (2017)
ABSTRACT Objective: To analyze alpha-linolenic fatty acid intake in two cohorts of pregnant women, and to identify factors associated with alpha-linolenic acid intake. Methods: This is a cohort study involving pregnant women with low obstetric risk (N=353) in public health system from a municipality of São Paulo state, Brazil. In each trimester, two 24-hour food recalls were collected. Descriptive analyses of dietary lipid profiles were performed, followed by a multiple comparison test. According to the trimester of pregnancy, differences were assessed using the mean difference test. To evaluate the adequacy of linoleic fatty acid and alpha-linolenic acid intake, the adequate intake test was used. The association between alpha-linolenic acid intake adequacy and maternal characteristics was investigated using a binary logistic regression model. Results: Total lipids intake and the percentage contribution to dietary energy met recommended levels. One-third of the diets demonstrated a lower than daily recommended intake of alpha-linolenic acid. Overweight pregnant women were twice as likely to have inadequate alpha-linolenic acid intake. Pregnant women from a more disadvantaged socioeconomic situation had greater risks of inadequate intake. Conclusion: Over-intake of lipids is not problematic, but quality is an issue, with one third of the pregnant women and their fetuses exposed to adverse effects due to low intake of omega-3 fatty acids, indicating important nutritional vulnerability in this population.